Structured white light scanning of rabbit Achilles tendon - Hayes, A.; Easton, K.; Devanaboyina, P.; Wu, Jian-Ping; Kirk, Brett; Lloyd, D. (Pergamon Press, 2016)
© 2016 Elsevier LtdBackground The cross-sectional area (CSA) of a material is used to calculate stress under load. The mechanical behaviour of soft tissue is of clinical interest in the management of injury; however, measuring CSA of soft tissue is challenging as samples are geometrically irregular and may deform during measurement. This study presents a simple method, using structured light scanning (SLS), to acquire a 3D model of rabbit Achilles tendon in vitro for measuring CSA of a tendon. Method The Artec Spider™ 3D scanner uses structured light and stereophotogrammetry technologies to acquire shape data and reconstruct a 3D model of an object. In this study, the 3D scanner was integrated with a custom mechanical rig, permitting 360-degree acquisition of the morphology of six New Zealand White rabbit Achilles tendons. The reconstructed 3D model was then used to measure CSA of the tendon. SLS, together with callipers and micro-CT, was used to measure CSA of objects with a regular or complex shape, such as a drill flute and human cervical vertebra, for validating the accuracy and repeatability of the technique. Results CSA of six tendons was measured with a coefficient of variation of less than 2%. The mean CSA was 9.9±1.0 mm2, comparable with those reported by other researchers. Scanning of phantoms demonstrated similar results to µCT. Conclusion The technique developed in this study offers a simple and accurate method for effectively measuring CSA of soft tissue such as tendons. This allows for localised calculation of stress along the length, assisting in the understanding of the function, injury mechanisms and rehabilitation of tissue.